2012
DOI: 10.1016/j.fuel.2012.06.063
|View full text |Cite
|
Sign up to set email alerts
|

Identification of operational regions in the Chemical-Looping with Oxygen Uncoupling (CLOU) process with a Cu-based oxygen carrier

Abstract: Chemical-Looping with Oxygen Uncoupling (CLOU) is an alternative chemical-looping process for the combustion of solid fuels with inherent CO 2 capture. The CLOU process demands a material as oxygen carrier with the ability to decompose with O 2 release at suitable temperatures for solid fuel combustion, e.g. copper oxide. This article presents an experimental method to determine the maximum oxygen generation rate of an oxygen carrier as well as to determine the minimum solid inventory that must be used in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 27 publications
5
76
0
Order By: Relevance
“…11) is lower than the solids inventory needed to reach a CO 2 capture higher than 95% without a carbon stripper (»600 kg/MW th ). This fact agree with previous results obtained from the analysis of the oxygen carrier reactivity [25] and results obtained in a CLOU unit [8,10]. It can be concluded that the kinetic parameters determined together with the simulation tool developed in this work, configure a useful instrument for the design and optimization of CLOU process.…”
Section:  supporting
confidence: 90%
See 4 more Smart Citations
“…11) is lower than the solids inventory needed to reach a CO 2 capture higher than 95% without a carbon stripper (»600 kg/MW th ). This fact agree with previous results obtained from the analysis of the oxygen carrier reactivity [25] and results obtained in a CLOU unit [8,10]. It can be concluded that the kinetic parameters determined together with the simulation tool developed in this work, configure a useful instrument for the design and optimization of CLOU process.…”
Section:  supporting
confidence: 90%
“…Thus, the kinetic model here proposed properly prediced the reaction rates when the O 2 concentrations was close to the equilibrium, where previous literature models had failed [15]. This condition is required in the fuel reactor of a CLOU unit to avoid unconverted compounds exiting the fuel reactor [8,25].…”
Section: Kinetic Information From Conversion Curvesmentioning
confidence: 84%
See 3 more Smart Citations